Reading Ability in Patients With Tuberous Sclerosis Complex: Results of Chinese Character Reading and Reading Comprehension Tests - Lee, Hom-Yi; Yang, Sheng-Hui; Sheu, Ji-Nan; Tsai, Jeng-Dau (Frontiers in Psychology, 2022)
Background: Most TSC patients have neurological disorders and are at high risk of academic difficulties. Among academic skills, reading ability is the most important academic skill. The study applied the Chinese character fluency test to measure the word recognition and reading comprehension of TSC children to observe whether they have the characteristics of reading disability, as an indicator of the spectrum of reading ability in TSC patients. Methods: The patients were assessed using the Chinese character fluency test and reading comprehension test to explore the differences in reading ability in terms of gender, age, epilepsy history, genotype, and intelligence level. Results: Of the 27 patients, the assessment of reading accuracy showed statistical differences between intellectual level > 80, PR (p=0.024), and pass numbers (p=0.018). For the fluency assessment, there was a difference between different intellectual level (p=0.050). In the reading comprehension test, there was differences for intellectual level in positivity (p=0.07) and pass numbers (p=0.06). Conclusions: The Chinese character fluency and reading comprehension test measure the word recognition and reading comprehension and the spectrum of reading ability in TSC patients. All individuals with TSC, especially those with below average of intellectual ability, should be considered for potential academic difficulties.